Listeria contamination in chevon and mutton from retail meat shops and slaughter house environment of Punjab, India. Issue 9 (27th May 2019) - Alka,; Singh, Randhir; Kaur, Simranpreet; Bedi, Jasbir Singh
ABSTRACT: Listeria monocytogenes is recognized as an emerging pathogen, with limited information or statistics on this pathogen. Moreover, poor hygienic practices in the unorganized meat sector favor its growth and survival. Therefore, the present study was carried out in Punjab, India to assess the prevalence of Listeria spp. in chevon and mutton samples, followed by its characterization. The prevalence of Listeria in chevon, mutton and swab samples collected from butchers' shops and slaughter houses was 1.82%, 3.21% and 6.66%, respectively. The 18 (2.67%) L. monocytogenes strains isolated from 786 samples carried one or more virulence-associated gene. Based on virulence genes, 6/18 isolates were potentially pathogenic. Serovar 4b (44.4%) was predominant, followed by serovars 1/2a (22.2%), 1/2b (22.2%) and 1/2c (11.1%). Detection of L . monocytogenes in meat and environment samples indicated poor hygiene, potential cross-contamination and risk of listeriosis to consumers and occupational workers. The findings of the study were also relevant to the fact that most of the slaughtering in Punjab, India is carried out in unorganized way, and this meat is not stored propery. Moreover, in the absence of a systematic foodborne disease surveillance and monitoring program, a database on foodborne diseases is absent, and needs to be established. Abstract : Pathogenic L. monocytogenes serotype 4b in meat and meat-processing environment of Punjab, India is a risk to consumers and occupational workers.